Komunikasi ibu dan anak dengan depresi pada remaja - Cilvia Nora, Ariza; Listyanti Widuri, Erlina (Universitas Ahmad Dahlan, 2011)
This study aims to determine the relationship between mother andchild communication with depression in adolescents. Samples of this studywere students of Sekolah Menengah Kejuruan Negeri 02 Depok(Sleman), Yogyakarta, 17-18 years old and living with parents. The numbersof samples in this study were 90 people. Quantitative analysis was carriedout using quantitative method; data was retrieved using a scale of depressionin adolescent and maternal and child communication scale. Data analysistechniques used was the Pearson correlation. The analysis indicated a highlysignificant negative relationship between maternal communication andchildren with depression in adolescents, with a correlation coefficient (r) =-0.325 with (p) = 0.002 (p <0.01). Maternal communication and childrencontributed in influencing depression in adolescents was 10.5%. Based onresearch that has been done, the researcher concluded that there was ahighly significant negative relationship between maternal communicationand children with depression in adolescents. The better communication isdone on the childs mother, the smaller the occurrence of depression inadolescents, whereas the lack of communication on the childs mothers,the greater occurrence of depression in adolescents.